The Healthy Start project: a randomized, controlled intervention to prevent overweight among normal weight, preschool children at high risk of future overweight - Olsen Nanna; Buch-Andersen Tine; Händel Mina; Østergaard Louise; Pedersen Jeanett; Seeger Charlotte; Stougaard Maria; Trærup Maria; Livemore Kate; Mortensen Erik; Holst Claus; Heitmann Berit (BMC, 2012)
Abstract Background Research shows that obesity prevention has to start early. Targeting interventions towards subgroups of individuals who are predisposed, but yet normal weight, may prove more effective in preventing overweight than interventions towards unselected normal weight subsets. Finally, interventions focused on other factors than diet and activity are lacking. The objectives were to perform a randomized, controlled intervention aiming at preventing overweight in children aged 2-6 years, who are yet normal weight, but have high predisposition for future overweight, and to intervene not only by improving diet and physical activity, but also reduce stress and improve sleep quality and quantity. Methods/Design Based on information from the Danish National Birth Registry and administrative birth forms, children were selected based on having either a high birth weight, a mother who was overweight prior to pregnancy, or a familial low socioeconomic status. Selected children (n = 5,902) were randomized into three groups; an intervention group, a shadow control group followed in registers exclusively, and a control group examined at the beginning and at the end of the intervention. Approximately 21% agreed to participate. Children who presented as overweight prior to the intervention were excluded from this study (n = 92). In the intervention group, 271 children were included, and in the control group 272 were included. Information obtained from the shadow control group is on-going, but it is estimated that 394 children will be included. The intervention took place over on average 1½ year between 2009 and 2011, and consisted of optional individual guidance in optimizing diet and physical activity habits, reducing chronic stress and stressful events and improving sleep quality and quantity. The intervention also included participation in cooking classes and play arrangements. Information on dietary intake, meal habits, physical activity, sleep habits, and overall stress level was obtained by 4-7 day questionnaire diaries and objective measurements. Discussion If the Healthy Start project is effective in preventing excessive weight gain, it will provide valuable information on new determinants of obesity which should be considered in future interventions, and on new strategies to prevent development of overweight and obesity at an early age. Trial registration ClinicalTrials.gov, ID NCT01583335.